PENGARUH GAYA HIDUP DAN SIKAP ETNOSENTRISME TERHADAP NIAT BELI KONSUMEN - Dewi, Ida Ayu Mas Laksmi; Sulistyawati, Eka (E-Jurnal Manajemen, 2016)
This study aims to describe the effect of lifestyle experiencers, lifestyle traditionalist, and ethnocentrism consumer attitudes towards consumer purchase intentions in Bali Alus products. Denpasar selected as the location of this study population used is the people who live in the city of Denpasar, at least 17 years old, tend to like taking care of themselves and have never bought a product Bali Alus. The sample was 115 people are determined using non-probability sampling and purposive sampling method. The research data come from questionnaires using 5-point Likert scale were distributed to the respondents and the data analysis technique used is multiple linear regression analysis and then the data is processed using SPSS for Windows 17.0. The results of their research analysis found positive and significant influence between lifestyles experiencers, lifestyle traditionalist and ethnocentric attitudes towards consumer purchase intentions in Denpasar on Bali Alus products. The implications are found in this research that consumers with traditionalist lifestyle has an the highest intention to buy product Bali Alus, then the second highest is the consumer with experiencers lifestyle and the lowest are consumers who have an attitude of ethnocentrism.
Keywords: Lifestyle, Experiencers, Traditionalist, ethnocentrism, Intention Buy